Feasibility analysis of treating severe intrauterine adhesions by transplanting menstrual blood-derived stem cells - Zheng, Sheng‑Xia; Wang, Jian; Wang, Xue‑Li; Ali, Asim; Wu, Li‑Min; Liu, Yu‑Sheng (International journal of molecular medicine, 2018)
Intrauterine adhesions (IUA) are associated with the loss of stem cells in the endometrium. Menstrual blood‑derived stem cells (MenSCs) can be isolated from the menstrual blood and differentiated into endometrial cells. To check the transplantation feasibility of MenSCs for the treatment of severe IUA, MenSCs were isolated from menstrual blood, cultured in Dulbecco's modified Eagle's medium (DMEM), identified by immunocytochemistry and flow cytometry, differentiated into endometrial cells in vitro, and finally transplanted into the axillary subcutaneous tissue of non‑obese diabetic/severe combined immunodeficiency (NOD‑SCID) mice to create endometrial tissue. Additionally, the cloning efficiency and POU domain class 5 transcription factor 1 (OCT‑4) positivity of MenSCs from patients with severe IUA were compared with those from healthy women. Immunocytochemistry and flow cytometry results showed that 95.1±0.8% cells were OCT‑4‑positive, 0.9±0.4% were cluster of differentiation (CD)45‑positive, 1.8±0.9% were STRO‑1‑positive and 1.0±0.4% were human leukocyte antigen‑antigen D related‑positive. Following differentiation in vitro, the results of immunocytochemistry, reverse transcription‑polymerase chain reaction and western blot analysis showed that the expression of cytokeratin (CK) and vimentin (VIM) was increased in MenSCs compared with that in control subjects. Subsequent to transplantation in mice administered with sequential 17β‑estradiol and progesterone, CK, VIM, estrogen receptor and progesterone receptor were expressed in the transplantation regions, suggesting that MenSCs could differentiate into endometrial tissues in vivo. The cloning efficiency and OCT‑4 positivity of MenSCs from patients with severe IUA was significantly decreased. In conclusion, to the best of our knowledge, this is the first study in which MenSCs could differentiate into endometrial cells in vitro and create endometrial tissue in NOD‑SCID mice in vivo, with impaired cloning efficiency and OCT‑4 expression of MenSCs from patients with IUA. This study will provide a theoretical basis for the treatment of IUA with MenSCs.